Periodisation of the philosophy of Islamic rationalism in the perspective of Zaki Naguib Mahmud - Supriyanto Supriyanto (HTS Teologiese Studies/Theological Studies, 2023)
In the current era of disruption, causality cannot be opposed to religion, so the independence of reason can contribute to the development of contemporary global thought in the Islamic world. This paper seeks to uncover the roots of the periodization of the philosophy of Islamic rationalism in the view of Zaki Naquib Mahmud. The primary data source is three books titled Arabiy baina Tsaqafatain, Tajdid Al-Fikr Al-Arabi, and Al-Ma’qul wa al-La Ma’qul fi Turatsina al-Fikribaik. Research data is a discourse that contains elements of religion and rationalism. The process of collecting data in this study is by studying literature and tracking various references related to the study’s focus. Data analysis techniques are carried out by the method of content analysis. Data validity using a triangulation model, by comparing data and relevant theory. The result of this study is that there are five phases of periodization of the philosophy of Islamic rationalism in the perspective of Zaki Naquib Mahmud, namely simple thinking [misykat] represented by Ali ibn Abi Talib; the lamp of reason [misbah] is characterized by the occurrence of philosophical debates about leadership and the great sin; the lamp glass [Zujajah al Misbah] is marked by the appearance of Bayt al-Ḥikmah in Baghdad; the luminous star [kaukab durriy] represented by the emergence of the Brotherhood of ash Shafa; and the endowed tree [syajarah mubarakah]. In this last phase, Zaki Naquib Mahmud positioned Ibn Rushd’s rationalism as an appropriate representation so as not to regress, even allowing for the realization of the renaissance in the Islamic world. This reflection of thought is expected to be able to inspire the millennial generation of Muslims about the importance of the philosophy of rationalism in the Islamic tradition